Neuroprotective effects of dried camu-camu (Myrciaria dubia HBK McVaugh) residue in C. elegans. (July 2015) - Azevêdo, Juliana C.S.; Borges, Kátia C.; Genovese, Maria I.; Correia, Roberta T.P.; Vattem, Dhiraj A.
Abstract: The effect of hot air dried camu-camu ( Myrciaria dubia HBK McVaugh) residue on modulating redox response signaling was evaluated in transgenic Caenorhabditis elegans . Camu-camu residue was fractionated into low and high molecular weight fractions and used as treatments. Relative fold changes in gene expression in response to camu-camu treatments were quantified using fluorescence microscopy. Also, the neuroprotective effects of camu-camu residue in experimentally induced neurodegeneration were evaluated in C. elegans models for Alzheimer's disease (AD) and Parkinson's disease (PD). For AD, time to thermally induced Aβ1–42 aggregation mediated paralysis was evaluated in transgenic C. elegans (CL4176). For PD, MPP + induced neurodegeneration was quantified by loss in motility due to paralysis. Results suggest a significant upregulation expression of superoxide dismutase (SOD-3 and SOD-4) and catalases (CTL-1; CTL-2; CTL-3) in response to treatment with camu-camu residue, especially with the low molecular weight fraction. Furthermore, treatment with this fraction significantly extended the life span in C. elegans by 20% and delayed Aβ1–42 induced paralysis by 21%. Additionally, treatment with camu-camu residue also abrogated MPP + induced neurodegeneration for PD by 15–21%. Highlights: Dried camu-camu residue extended the lifespan in C. elegans . Treatments with dried camu-camu residue increased the expression of antioxidant genes. Dried camu-camu residue promoted significant decreased neurotoxicity in C. elegans . Dried camu-camu residue is a bioactive-rich product with health-relevant potential.